Resource Manual for the Development of Cooperative Vocational Education Programs under the Vocational Education Act of 1963, As Amended P. L. 90-576 - Bureau of Adult, Vocational, and Technical Education (DHEW/OE), Washington, DC.; Bureau of Adult, Vocational, and Technical Education (DHEW/OE), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
This booklet summarizes selected facts and suggestions for the use of State staffs in planning for the development of cooperative vocational education programs under Public Law 90-576. Designed to provide pertinent information as technical assistance for facilitating the decision-making process, this resource manual is intended for use in conjunction with "A Guide for Cooperative Vocational Education," (ED 037 564) published by the University of Minnesota. Term definitions, funding sources for cooperative education, selected regulations for State vocational education programs, allowable expenditures of Federal and matching funds, persons served by cooperative programs, and additional programmatic information are included. A comparative analysis of State, cooperative, and work-study programs for vocational education is presented in a 3-column format. The resource materials were prepared by an education program specialist, under the direction of the chief of state programs and services. (AG)
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Development; Comparative Analysis; Cooperative Programs; Educational Finance; Financial Support; Program Development; Resource Materials; Secondary Education; State Programs; Vocational Education; Work Study Programs; Vocational Education Amendments 1968; Decisions -- Educational Awareness -- Vocational Education Act 1963